PENGARUH FLUKTUASI HARGA TERHADAP KESEJAHTERAAN PETANI PERSPEKTIF EKONOMI SYARIAH - Siswanto, Siswanto; Cahyoningtyas, Retno; Andriyani, Fitri; Hadi, Luqman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the effect of price fluctuations on the welfare of janggelan farmers from a sharia economic perspective in Gondang Village. This study uses a quantitative approach with a descriptive research type. The data source in this study is primary data, namely data obtained directly from respondents through questionnaires. The population in this study includes all janggelan farmers in Nawangan District. The sample determination was carried out using a sampling technique, namely purposive sampling, where the sample was determined based on the criteria, considerations and objectives of the researcher. The data collected through the questionnaire were then analyzed using descriptive and inferential statistical methods, namely Simple Regression Analysis. The regression coefficient value of the Janggelan Price Fluctuation (X) variable of 0.438 indicates that the X variable has a positive influence on the Farmer Welfare variable (Y). Meanwhile, the Adjusted R-Square determination coefficient value of 0.741 indicates that 74.1% of the variation in the Janggelan Farmer Welfare variable can be explained by the Janggelan Price Fluctuation variable. The significance value of variable X is 0.000 < 0.05, indicating that the effect is statistically significant. Thus, the hypothesis that Janggelan Price Fluctuations have a positive effect on Janggelan Farmers' Welfare is valid.